Performance of Nonuniform PAM Constellations for Gaussian Channel - Perić, Z. H.; Bogosavljević, S. M. (Elektronika ir Elektrotechnika, 2004)
In this paper, the Gaussian source quantization is done by using three different quantization methods[1,2]. Weanalyzed Pulse Amplitude Modulation (PAM) signal constellation obtained by means of different quantization methods for Gaussianchannel. Also this paper presents the analysis method for the determination of the optimal signal constellation points disposition afterquantization, when the error probability is minimized under the power constraint [3,4]. In order to investigate the quantization influenceon symbol error probability for the Gaussian channel, Re- optimal quantization method. Ill. 6, bibl. 6 (in English; summaries inLithuanian, English and Russian).